2020
DOI: 10.3389/fphar.2020.00082
|View full text |Cite
|
Sign up to set email alerts
|

Morphine Addiction and Oxidative Stress: The Potential Effects of Thioredoxin-1

Abstract: Long-term administration of morphine for the management of chronic pain will result in tolerance to its analgesic effect and could even cause drug dependence. Numerous studies have demonstrated significant redox alteration in morphine dependence and addiction. Thioredoxin-1 (Trx-1) play important roles in controlling the cellular redox balance. In recent years, several recent studies have demonstrated that Trx-1 may be a promising novel therapeutic target for morphine addiction. In this article, we firstly rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 64 publications
1
32
0
Order By: Relevance
“…2 ). The protection of Sal at 50 μM was better than that of Geranylgeranylacetone (GGA), which is a Trx inducer and a protective agent against MPP + 12 , 24 . However, the protective effect of Sal was inhibited by co-treated with 2-[(1-Methylpropyl) dithio]-1H-imidazole (PX-12), a Trx1 inhibitor 25 , 26 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 ). The protection of Sal at 50 μM was better than that of Geranylgeranylacetone (GGA), which is a Trx inducer and a protective agent against MPP + 12 , 24 . However, the protective effect of Sal was inhibited by co-treated with 2-[(1-Methylpropyl) dithio]-1H-imidazole (PX-12), a Trx1 inhibitor 25 , 26 .…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that Trx1 was involved in the protective effect of Sal against MPP + -induced apoptosis in SH-SY5Y cells. GGA is a Trx1 inducer and has a protective agent against MPP + 12 , 24 . In the present study, the protective effect of Sal (50 μM) was similar to that of GGA.…”
Section: Discussionmentioning
confidence: 99%
“…Trx couples with Prx to scavenge ROS, such as directly converting H 2 O 2 to H 2 O (Granger and Kvietys, 2015). Our previous studies demonstrated that Trx exerted protective effects in oxidative stress, morphine and methamphetamine addiction, autoimmune disease, cerebral ischemic damage and cancers (Chen et al., 2014; Zeng, Zhou, et al., 2014; Zeng et al., 2015; Jia et al., 2019; L. Yang et al., 2020; Zeng et al., 2020). Trx was reported to improve the learning and memory ability of Parkinsonism mice (X.…”
Section: Trxs In Admentioning
confidence: 99%
“…Our results have shown that NR1 can induce the expression of Trx-1. Trx-1 played a vital role in various diseases, including ischemic stroke ( Qi et al, 2015 ), morphine addiction ( Zeng et al, 2020 ), and Parkinson’s disease ( Zeng et al, 2014 ). Besides, Wang et al proved that NR1 alleviated ROS which was induced by high glucose present in RSC96 cells ( Wang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%